2016
DOI: 10.14358/pers.82.12.973
|View full text |Cite
|
Sign up to set email alerts
|

Improved Urban Scene Classification Using Full-Waveform Lidar

Abstract: Full-waveform lidar data provides supplementary radiometric as well as more accurate geometric target information, when compared to discrete return systems. In this research, a wide range of classes in an urban scene; including trees, medium vegetation, low vegetation (grass), water bodies, pitched roofs, flat roofs, asphalt, vehicles, power lines, walls (fences) and concrete are considered. In order to tackle the challenge of distinguishing geometrically similar classes and enhancing the separability of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Some of the existing remote sensing studies implement the random undersampling (RUS) method [19], which randomly reduces the number of the majority class training samples. However, this method has the disadvantage of information loss, as it discards samples from the majority class [5].…”
Section: Random Resamplingmentioning
confidence: 99%
“…Some of the existing remote sensing studies implement the random undersampling (RUS) method [19], which randomly reduces the number of the majority class training samples. However, this method has the disadvantage of information loss, as it discards samples from the majority class [5].…”
Section: Random Resamplingmentioning
confidence: 99%
“…Nevertheless, some research studies have developed FWA techniques to derive more accurate basic features as well as some advanced features from the backscattered signal [12]. Studies have shown that employing basic and advanced waveform features along with careful radiometric calibration of the data improves multiclass classification in urban areas [12,13,29]. Furthermore, adding features such as the total number of echoes within each waveform and the position of the echo in the waveform together with some geometric and/or spectral features derived from the lidar system or integrated sensors such as multispectral or hyperspectral cameras can significantly increase the accuracy of the multi-class classification of lidar data over complex environments [5,22,30,31].…”
Section: A Waveform Features For Classificationmentioning
confidence: 99%
“…Khoshelham et al (2013) and Weinmann et al (2015) used feature selection methods to reduce the required number of training samples. Azadbakht et al (2016) investigated different sampling strategies to overcome an imbalance in the distribution of training samples. In this paper, we propose a two-step classification method for distinguishing similar objects with insufficient and unbalanced training data.…”
Section: Literature Reviewmentioning
confidence: 99%